The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
SciVee 2010
DOI: 10.4016/19865.01
|View full text |Cite
|
Sign up to set email alerts
|

Social Relationships and Mortality Risk: A Meta-analytic Review

Abstract: Background: The quality and quantity of individuals' social relationships has been linked not only to mental health but also to both morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
757
2
22

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 785 publications
(810 citation statements)
references
References 30 publications
29
757
2
22
Order By: Relevance
“…Likewise, viewing social stress or social isolation as a physiological phenomenon, as well as a psychological phenomenon, may help us to better understand the robust relationships between social ties and health (Holt-Lunstad et al, 2010). A better understanding of the co-regulation of inflammation and social behavior may bring us a step closer to these goals.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, viewing social stress or social isolation as a physiological phenomenon, as well as a psychological phenomenon, may help us to better understand the robust relationships between social ties and health (Holt-Lunstad et al, 2010). A better understanding of the co-regulation of inflammation and social behavior may bring us a step closer to these goals.…”
Section: Resultsmentioning
confidence: 99%
“…Romantic love is one of the most powerful motivators of human behavior and has been linked to physical and mental health (Holt-Lunstad et al, 2010). Grief over the loss of a partner is considered a major adverse life event associated with an elevated risk for stress-related psychiatric disorders (Lundin, 1984;Keyes et al, 2014), acute myocardial infarction in men (Mostofsky et al, 2012) and breast cancer in women (Lillberg et al, 2003;Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that loneliness can worsen health-related problems (Hawkley and Cacioppo 2010;Sugisawa et al 1994;Thurston and Kubzansky 2009). Indeed, one study showed that lonely people have a 45% higher mortality rate than people who are not lonely (Holt-Lunstad et al 2010). How does the pursuit of an entrepreneurial career influence healthrelated loneliness?…”
Section: Health and Entrepreneurial Motivationmentioning
confidence: 99%